52nd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2011
DOI: 10.2514/6.2011-2170
|View full text |Cite
|
Sign up to set email alerts
|

Compression Behavior of Fluted-Core Composite Panels

Abstract: In recent years, fiber-reinforced composites have become more accepted for aerospace applications. Specifically, during NASA's recent efforts to develop new launch vehicles, composite materials were considered and baselined for a number of structures. Because of mass and stiffness requirements, sandwich composites are often selected for many applications. However, there are a number of manufacturing and in-service concerns associated with traditional honeycomb-core sandwich composites that in certain instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…With the exception of the curvature, these are essentially the same dimensions as the subscale test articles discussed in Ref. 3 and the curved panel of Ref. 4., and the cylinder described herein is representative of the test article shown in Fig.…”
Section: Fluted-core Sandwich Cylinder Definitionmentioning
confidence: 81%
See 4 more Smart Citations
“…With the exception of the curvature, these are essentially the same dimensions as the subscale test articles discussed in Ref. 3 and the curved panel of Ref. 4., and the cylinder described herein is representative of the test article shown in Fig.…”
Section: Fluted-core Sandwich Cylinder Definitionmentioning
confidence: 81%
“…Therefore, most structural analysts will be able to use it to analyze fluted-core structure. However, it has been shown that detailed analysis of the fluted-core can require very complex models; 3,4 this suggests finite-element analysis is generally well suited for the final detailed design phase of the DAC, where a final design is being analyzed to ensure it satisfies the requirements. It was demonstrated that relatively simple finite-element models can be used to analyze the fluted-core for basic response, such as global and local buckling, and overall strain requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations